Vikramāṅkadevacaritacarcā, arthāt, Mahākavi Bilhaṇa kr̥ta Vikramāṅkadevacarita kāvya kī ālocanā - Dwivedi, Mahavir Prasad (SAMP early 20th-century Indian books project ;, 1910)
Study of Vikramāṅkadevacarita of Bilhaṇa, 11th cent. Sanskrit author.